In vitro comparative analysis of antiproliferative activity of essential oil from mandarin peel and its principal component limonene - Manassero, Carlos Alberto (2012)
The effects of the essential oil of mandarin peel (Corrientes, Argentina) and limonene (its major component) were studied on two human tumour cell lines growth (lung adenocarcinoma A549 and hepatocarcinoma HepG2). The essential oil was obtained by cold press and its composition was investigated by gas chromatography (GC) and GC/mass spectrometry (MS) analysis. The antiproliferative effect was studied using an MTT assay. Both mandarin essential oil and limonene tested showed a strong dose-dependent effect on the growth inhibition of these cell lines. The essential oil was more effective in A549 than in HepG2 cells and more effective than limonene in both the cases. It is likely that minor components and limonene of the oil could exert additive or synergistic effects. Hence, mandarin essential oil could lead to the development of anti-tumour agent or complementary and alternative medicines for the treatment of diverse cancers.